Silicon-carbon negative electrode material and preparation method and application thereof
By dispersing the silicon source in porous carbon materials, the silicon carbon negative electrode material is prepared, which solves the problem of high volume expansion rate of silicon-based negative electrode materials during charging and discharging, significantly improves the energy density and cycle life of lithium batteries, and achieves high Performance and low cost production.
Patent Information
- Application Number
- CN202411937713.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The theoretical specific capacity of traditional graphite negative electrode materials is low and cannot meet the needs of high-energy-density batteries. The volume expansion rate of silicon-based negative electrode materials during charging and discharging is high, resulting in poor cycle stability, electrical contact loss and repeated formation of SEI films, limiting the Its commercial application.
By dispersing the silicon source in the porous carbon material, using the emulsion method and chemical vapor deposition method, a silicon carbon negative electrode material is prepared to provide the volume expansion space of silicon, reduce agglomeration and powdering, and enhance structural stability.
Silicon-carbon anode material significantly improves the energy density and cycle life of lithium batteries, has excellent electrochemical performance and stability, is suitable for industrial production, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode material preparation, and specifically relates to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the growing demand for energy, lithium-ion batteries, as high-energy-density energy storage devices, have been widely used in smart phones, laptops, and even electric vehicles. However, traditional graphite anode materials can no longer meet the market demand for higher energy-density batteries due to their low theoretical specific capacity (about 372 mAh / g). Silicon, as a material with a high theoretical specific capacity (about 4200 mAh / g), is considered to be an ideal alternative to anode materials. However, the volume expansion rate of silicon during the charge and discharge process is as high as 300%, which leads to poor cycle stability of silicon anode materials, electrical contact loss, and repeated formation of SEI film, thus limiting its commercial application.
[0003] In order to solve the above problems, researchers have developed a variety of methods for preparing silicon-based negative electrode materials, including chemical vapor deposition, mechanical ball milling and sol-gel methods, in order to reduce the negative impact of volume changes by nano-siliconization, carbon coating or adding silicon dioxide. However, compared with graphite negative electrode materials, the preparation process of silicon-based negative electrode materials is complex, large-scale production has certain difficulties, the cost is high, and the products are not yet standardized.
[0004] In addition, in order to improve the energy density of lithium-ion batteries, researchers are also exploring various ways such as improving battery structure design, electrolyte innovation, and optimizing battery management systems. For example, battery performance can be improved by increasing the proportion of active substances in electrodes, using new conductive agents and binders, and increasing the coating amount of positive and negative electrodes. At the same time, the development of high-concentration electrolytes or new solvent systems can broaden the electrochemical window of batteries, increase the operating voltage, and thus increase energy density. Summary of the invention
[0005] The present invention aims to provide a silicon-carbon negative electrode material and a preparation method and application thereof. The method can provide space for the volume expansion of silicon and reduce agglomeration and pulverization during the cycle process. The silicon-carbon negative electrode material is used in lithium batteries to improve the energy density and cycle life of lithium batteries.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a silicon-carbon negative electrode material comprises the following steps: S1, adding porous carbon material and silicon source into deionized water, stirring to obtain a mixed solution; S2, adding a surfactant and a silane coupling agent to the mixed solution obtained in step S1, ultrasonically dispersing, mixing, vacuum heating, and stirring at 2500-8000 rpm for 2 min to obtain an emulsion; S3, transferring the emulsion obtained in S2 to a 100 mL polytetrafluoroethylene-lined autoclave, introducing ammonia gas, and heating for reaction to obtain a porous carbon silicon material; S4, in a nitrogen environment, introducing an organic silicon source gas to perform a chemical vapor deposition reaction on the porous carbon silicon material obtained in step S3 to obtain a silicon-carbon negative electrode material precursor; S5. In a nitrogen environment, introduce a carbon source to carry out carbon precipitation reaction on the silicon-carbon negative electrode material precursor obtained in step S4, cool to room temperature, wash three times with deionized water and anhydrous ethanol respectively, place in an oven at 60-80°C and dry for 6-8h to obtain a silicon-carbon negative electrode material.
[0007] Preferably, in step S1, the porous carbon material includes one or more of activated carbon, carbon nanotubes, and ordered mesoporous carbon material CMK-3.
[0008] Preferably, in step S1, the porous carbon material has a pore size of 2-60 nm and a specific surface area of 100-3000 m 2 / g.
[0009] Preferably, in step S1, the silicon source includes one or more of SiH4, SiCl4, and SiF4, and the purity of the silicon source is greater than 99.9%.
[0010] Preferably, in step S1, the mass ratio of the porous carbon material to the silicon source is (20:1)-(50:3).
[0011] Preferably, in step S2, the surfactant includes one of Span 80 or hexadecyltrimethylammonium bromide, and the silane coupling agent includes one of KH-550, KH-560 or A-1100.
[0012] Preferably, in step S2, the amount of the surfactant added is 0.1%-5% of the porous carbon material, and the amount of the silane coupling agent added is 0.5%-10% of the porous carbon material.
[0013] Preferably, in step S2, the ultrasonic dispersion is specifically as follows: the ultrasonic frequency is 20-30 kHz, the ultrasonic power is 200-250 W, the ultrasonic temperature is 20-30° C., and the ultrasonic time is 15-20 min.
[0014] Preferably, in step S2, the vacuum degree is 100-120 Pa, the heating temperature is 60-70° C., and the heating time is 20-35 min.
[0015] Preferably, in step S3, the ammonia gas flow rate is 0.5-2 L / min, the reaction temperature is 90-240° C., and the reaction time is 0.5-5 h.
[0016] Preferably, in step S4, the organic silicon source gas is one of silane, dichlorosilane, silicon tetrafluoride, and disilane.
[0017] Preferably, in step S4, the flow rate of the organosilicon source gas is 2-6 L / min, the chemical vapor deposition reaction temperature is 500-850° C., and the reaction time is 60-180 min.
[0018] In step S5, the carbon source includes one of methane, ethane, acetylene, propane, propylene, and acetone.
[0019] In step S5, the carbon source gas flow rate is 2-5 L / min, the carbon deposition temperature is 600-800° C., and the reaction time is 120-240 min.
[0020] The present invention also provides a silicon-carbon negative electrode material prepared by the preparation method.
[0021] The present invention also provides a silicon-carbon negative electrode material prepared by the preparation method or application of the silicon-carbon negative electrode material in a lithium-ion battery.
[0022] The present invention also provides a lithium ion battery, comprising the silicon-carbon negative electrode material prepared by the preparation method or the silicon-carbon negative electrode material.
[0023] Compared with the prior art, the present invention has the following advantages and technical effects: (1) The present invention discloses a silicon-carbon negative electrode material and its preparation method and application. By dispersing silicon sources in porous carbon materials, a buffer space is provided for the volume expansion of silicon during the charging and discharging process, which effectively reduces the agglomeration and pulverization of silicon particles and enhances the structural stability of the negative electrode material.
[0024] (2) The silicon-carbon negative electrode material prepared by the present invention exhibits excellent electrochemical properties, including higher specific capacity, excellent first coulombic efficiency and outstanding cycle stability. These performance improvements are due to the synergistic effect of silicon and carbon materials and precisely controlled preparation conditions.
[0025] (3) The silicon-carbon negative electrode material of the present invention can significantly improve the energy density of the battery and meet the market demand for high-energy batteries. At the same time, a uniform carbon layer covers the surface of the silicon-carbon negative electrode material precursor, effectively protecting the silicon core and reducing the erosion of the electrolyte, thereby extending the cycle life of the battery. The preparation method of the present invention is scalable, suitable for industrial production, and the raw materials are easily available and the cost is controllable, which helps to reduce the production cost of high-performance lithium batteries.
[0026] (4) The silicon-carbon negative electrode material provided by the present invention has excellent stability, and the battery can operate under a wider range of temperature and operating conditions, thereby improving the environmental adaptability and application range of the battery.
[0027] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further illustrated by the following embodiments.
[0029] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0030] In the present invention, unless otherwise specified, other test materials and instruments and equipment are conventional test materials in the art and can be purchased through commercial channels.
[0031] Embodiment 1 This embodiment provides a silicon-carbon negative electrode material, and the preparation method includes the following steps: S1. Add 20 mg of carbon nanotubes (pore size of 20 nm, specific surface area of 100 m2) into 15 mL of deionized water. 2 / g) and 1mg SiCl4 (purity greater than 99.9%) were stirred for 30min to obtain a mixed solution; S2, adding 1 mg of hexadecyltrimethylammonium bromide and 2 mg of KH-550 to the mixed solution obtained in step S1, ultrasonically dispersing for 15 min at 30 kHz, 250 W, and 30° C., mixing, vacuum heating at 120 Pa and 60° C. for 35 min, and stirring at 8000 rpm for 2 min to obtain an emulsion; S3, transferring the emulsion obtained in S2 to a 100 mL polytetrafluoroethylene-lined autoclave, introducing ammonia gas at a gas flow rate of 0.5 L / min, heating at 150° C. for 1 h to obtain a porous carbon silicon material; S4, in a nitrogen environment, introducing silane at a gas flow rate of 2 L / min, and subjecting the porous carbon-silicon material obtained in step S3 to a chemical vapor deposition reaction at 600° C. for 120 min to obtain a silicon-carbon negative electrode material precursor; S5. In a nitrogen environment, methane is introduced at a gas flow rate of 2 L / min, and the silicon-carbon negative electrode material precursor obtained in step S4 is subjected to carbon precipitation reaction at 750°C for 180 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 6 h to obtain a silicon-carbon negative electrode material.
[0032] Embodiment 2 This embodiment provides a silicon-carbon negative electrode material, and the preparation method includes the following steps: S1. Add 50 mg of ordered mesoporous carbon material CMK-3 (pore size of 4 nm, specific surface area of 900 m2) into 30 mL of deionized water. 2 / g) and 3mg SiCl4 (purity greater than 99.9%) were stirred for 30min to obtain a mixed solution; S2, adding 2.5 mg of hexadecyltrimethylammonium bromide and 3 mg of KH-560 to the mixed solution obtained in step S1, ultrasonically dispersing for 20 min at 25 kHz, 230 W, and 25° C., mixing, vacuum heating at 120 Pa and 70° C. for 20 min, and stirring at 8000 rpm for 2 min to obtain an emulsion; S3, transferring the emulsion obtained in S2 to a 100 mL polytetrafluoroethylene-lined autoclave, introducing ammonia gas at a gas flow rate of 0.5 L / min, heating at 120° C. for 3 h to obtain a porous carbon silicon material; S4, in a nitrogen environment, disilane is introduced at a gas flow rate of 3 L / min, and the porous carbon silicon material obtained in step S3 is subjected to a chemical vapor deposition reaction at 800° C. for 90 min to obtain a silicon-carbon negative electrode material precursor; S5. In a nitrogen environment, methane is introduced at a gas flow rate of 2 L / min, and the silicon-carbon negative electrode material precursor obtained in step S4 is subjected to carbon precipitation reaction at 800°C for 150 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 6 h to obtain a silicon-carbon negative electrode material.
[0033] Embodiment 3 This embodiment provides a silicon-carbon negative electrode material, and the preparation method includes the following steps: S1. Add 80 mg of activated carbon (pore size of 30 nm, specific surface area of 800 m2) into 50 mL of deionized water. 2 / g) and 4mg SiCl4 (purity greater than 99.9%) were stirred for 30min to obtain a mixed solution; S2, adding 3 mg Span 80 and 6 mg A-1100 to the mixed solution obtained in step S1, ultrasonically dispersing for 20 min at 20 kHz, 250 W, and 20° C., mixing, vacuum heating at 120 Pa and 70° C. for 20 min, and stirring at 8000 rpm for 2 min to obtain an emulsion; S3, transferring the emulsion obtained in S2 to a 100 mL polytetrafluoroethylene-lined autoclave, introducing ammonia gas at a gas flow rate of 0.5 L / min, heating at 240° C. for 0.5 h to obtain a porous carbon silicon material; S4, in a nitrogen environment, introduce dihydrogen dichlorosilane at a gas flow rate of 4 L / min, and perform chemical vapor deposition reaction on the porous carbon silicon material obtained in step S3 at 850° C. for 60 min to obtain a silicon-carbon negative electrode material precursor; S5. In a nitrogen environment, ethane is introduced at a gas flow rate of 3 L / min, and the silicon-carbon negative electrode material precursor obtained in step S4 is subjected to carbon precipitation reaction at 800°C for 150 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 6 h to obtain a silicon-carbon negative electrode material.
[0034] Comparative Example 1 S1. Add 20 mg of carbon nanotubes (pore size of 20 nm, specific surface area of 100 m2) into 15 mL of deionized water. 2 / g) and 1mg SiCl4 (purity greater than 99.9%) were stirred for 30min to obtain a mixed solution; S2, transferring the mixed solution obtained in S1 to a 100 mL polytetrafluoroethylene-lined autoclave, heating at 150° C. for 1 h to obtain a carbon silicon material; S3, in a nitrogen environment, introducing silane at a gas flow rate of 2 L / min, and subjecting the carbon-silicon material obtained in step S2 to a chemical vapor deposition reaction at 600° C. for 120 min to obtain a silicon-carbon negative electrode material precursor; S4. In a nitrogen environment, methane is introduced at a gas flow rate of 2 L / min, and the silicon-carbon negative electrode material precursor obtained in step S4 is subjected to carbon precipitation reaction at 750°C for 180 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 6 h to obtain a silicon-carbon negative electrode material.
[0035] Comparative Example 2 S1. Add 50 mg of ordered mesoporous carbon material CMK-3 (pore size of 4 nm, specific surface area of 900 m2) into 30 mL of deionized water. 2 / g) and 3mg SiCl4 (purity greater than 99.9%) were stirred for 30min to obtain a mixed solution; S2, adding 2.5 mg of hexadecyltrimethylammonium bromide and 3 mg of KH-560 to the mixed solution obtained in step S1, ultrasonically dispersing for 20 min at 25 kHz, 230 W, and 25° C., mixing, vacuum heating at 120 Pa and 70° C. for 20 min, and stirring at 8000 rpm for 2 min to obtain an emulsion; S3, transferring the emulsion obtained in S2 to a 100 mL polytetrafluoroethylene-lined autoclave, heating and reacting at 120° C. for 3 h to obtain a porous carbon silicon material; S4. In a nitrogen environment, disilane is introduced at a gas flow rate of 3 L / min, and the porous carbon silicon material obtained in step S3 is subjected to a chemical vapor deposition reaction at 800° C. for 90 min to obtain a silicon-carbon negative electrode material.
[0036] Comparative Example 3 S1. Add 80 mg of activated carbon (pore size of 30 nm, specific surface area of 800 m2) into 50 mL of deionized water. 2 / g) and 4mg SiCl4 (purity greater than 99.9%) were stirred for 30min to obtain a mixed solution; S2, adding 3 mg Span 80 and 6 mg A-1100 to the mixed solution obtained in step S1, ultrasonically dispersing for 20 min at 20 kHz, 250 W, and 20° C., mixing, vacuum heating at 120 Pa and 70° C. for 20 min, and stirring at 8000 rpm for 2 min to obtain an emulsion; S3, transferring the emulsion obtained in S2 to a 100 mL polytetrafluoroethylene-lined autoclave, introducing ammonia gas at a gas flow rate of 0.5 L / min, heating at 400° C. for 0.5 h, and obtaining a porous carbon silicon material; S4, in a nitrogen environment, introduce dihydrogen dichlorosilane at a gas flow rate of 4 L / min, and perform chemical vapor deposition reaction on the porous carbon silicon material obtained in step S3 at 950° C. for 100 min to obtain a silicon-carbon negative electrode material precursor; S5. In a nitrogen environment, ethane is introduced at a gas flow rate of 3 L / min, and the silicon-carbon negative electrode material precursor obtained in step S4 is subjected to carbon precipitation reaction at 900°C for 180 min. The product is cooled to room temperature, washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C for 6 h to obtain a silicon-carbon negative electrode material.
[0037] The effects of the silicon-carbon negative electrode materials provided in the above embodiments and comparative examples were verified by the following experiments: The negative electrode materials provided in the above embodiments and comparative examples are prepared into a lithium ion battery, comprising the following steps: The button cell was assembled in a glove box (water and oxygen content were both less than 0.01 ppm).
[0038] The prepared negative electrode material was used as the negative electrode active material, and was weighed in sequence with acetylene black and polyvinylidene fluoride in a mass ratio of 8:2:1. After being fully ground in an agate mortar, an appropriate amount of N-methylpyrrolidone was added to mix into a uniform slurry. The slurry was evenly coated on a copper foil using an infrared drying coater and dried at 120°C for 45 minutes to obtain a dry electrode sheet. The dry electrode sheet was rolled and cut by a roller press to obtain a negative electrode sheet with a diameter of 12 nm. The negative electrode active material loading of each negative electrode sheet was 0.9 mg cm -2. The positive electrode uses a metal lithium sheet (diameter 12 mm, thickness 0.5 mm), the separator is glass fiber (Whatman, 20 mm), and the electrolyte is 1 M LiPF6 (dissolved in a mixed solvent of EC:DMC = 1:1). The negative electrode sheet, electrolyte, separator, electrolyte and metal lithium sheet are assembled in this order, and then sealed with a hydraulic sealing machine to obtain a lithium-ion battery for charge and discharge tests. The voltage range is 5mV-1.5V and the current density is 80mA / g. The performance parameters of the lithium-ion battery obtained are tested, such as the charge and discharge capacity, cycle performance, and first efficiency. The results are shown in Table 1.
[0039] Table 1 Electrochemical properties of lithium-ion batteries
[0040] As can be seen from Table 1, Examples 1-3 are superior to Comparative Examples 1-3 in the three key performance indicators of first reversible capacity, first efficiency, and 500 cycles of charge and discharge capacity retention. This shows that the silicon-carbon negative electrode materials prepared in Examples 1-3 have significant advantages in battery performance and can provide higher energy density and longer cycle life. Among them, the silicon-carbon negative electrode material provided in Example 2 performs best in all indicators and achieves the best balance in battery performance.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The steps include: S1. Adding porous carbon material and silicon source into deionized water and stirring to obtain a mixed solution; S2, adding a surfactant and a silane coupling agent to the mixed solution obtained in step S1, ultrasonically dispersing, mixing, vacuum heating, and stirring at 2500-8000 rpm for 2 min to obtain an emulsion; S3, transferring the emulsion obtained in S2 to a 100 mL polytetrafluoroethylene-lined autoclave, introducing ammonia gas, and heating for reaction to obtain a porous carbon silicon material; S4, in a nitrogen environment, introducing an organic silicon source gas to perform a chemical vapor deposition reaction on the porous carbon silicon material obtained in step S3 to obtain a silicon-carbon negative electrode material precursor; S5. In a nitrogen environment, introduce a carbon source to carry out carbon precipitation reaction on the silicon-carbon negative electrode material precursor obtained in step S4, cool to room temperature, wash three times with deionized water and anhydrous ethanol respectively, place in an oven at 60-80°C and dry for 6-8h to obtain a silicon-carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the porous carbon material to the silicon source is (20:1)-(50:3).
3. The preparation method according to claim 1, characterized in that: In step S2, the ultrasonic dispersion is specifically as follows: the ultrasonic frequency is 20-30 kHz, the ultrasonic power is 200-250 W, the ultrasonic temperature is 20-30° C., and the ultrasonic time is 15-20 min.
4. The preparation method according to claim 1, characterized in that: In step S2, the vacuum degree is 100-120 Pa, the heating temperature is 60-70° C., and the heating time is 20-35 min.
5. The preparation method according to claim 1, characterized in that: In step S3, the ammonia gas flow rate is 0.5-2 L / min, the reaction temperature is 90-240° C., and the reaction time is 0.5-5 h.
6. The preparation method according to claim 1, characterized in that: In step S4, the flow rate of the organosilicon source gas is 2-6 L / min, the chemical vapor deposition reaction temperature is 500-850° C., and the reaction time is 60-180 min.
7. The preparation method according to claim 1, characterized in that: In step S5, the carbon source gas flow rate is 2-5 L / min, the carbon deposition temperature is 600-800° C., and the reaction time is 120-240 min.
8. The silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or the silicon-carbon negative electrode material according to claim 8 in a lithium-ion battery.
10. A lithium ion battery, characterized in that: The silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or the silicon-carbon negative electrode material according to claim 8.
Citation Information
Patent Citations
A silicon-carbon composite negative electrode material and a preparation method thereof
CN109004203A
A preparation method of a silicon clad composite material based on porous carbon
CN109037620A
Silicon-carbon anode material for lithium ion battery and preparation method thereof
CN110400930A
Porous silicon-carbon lithium ion battery anode material with high rate capability and preparation method thereof
CN110600719A
Porous carbon doping induced silicon deposition silicon-carbon negative electrode material and preparation method thereof
CN114122352A